An approach for obtaining mechanical property of austenitic stainless steel by using continuous indentation test analysis. (December 2020) - Xue, He; He, Jinxuan; Jia, Wenna; Zhang, Jianlong; Wang, Shuai; Zhang, Shun; Yang, Hongliang; Wang, Zheng
Abstract: It is importance to understand the accurate material mechanical property of local area with flaws in the structure integrity evaluation, and the plastic hardening induced by the welding or other processing would induce the change of the mechanical property of the local area in structures. To understand and obtain heterogeneous material mechanical properties in the welded joint or other local region in the core structure of nuclear power plants, a group tests of tensile work hardening and continuous ball indentation, combining with inversion analysis by using the finite element method, are used to obtain the local mechanical properties of nuclear grade 316L austenitic stainless steel, and an approach to obtain the stress–strain relationship of the stainless steel material during the plastic deformation stage under different elongations is developed based on the representative stress–strain method in this paper. The investigated results indicates that the related mechanical parameters of 316L austenitic stainless steel increase with different elongations, and the deviations of the yield strength and the tensile strength values are both within 6%. It provides a reasonable and effective method to obtain the actual material mechanical property of the local area in important structures.